Exploring multimodal literacy through digital gameplay and analysis---Chinese adolescents’ learning experience - Shen, Yanan; Ab Jalil, Habibah; Jamaluddin, Rahimah (Ani Publishing, 2024)
Purpose: Academic discourse underscores the potential of digital gameplay in facilitating adolescents' acquisition of multimodal literacy. Despite the enduring appeal of digital games among this demographic, their pedagogical merits remain predominantly overlooked and underutilized. Thus, this investigation seeks to delve into the realm of Chinese secondary students' multimodal literacy acquisition facilitated by engagement with digital gaming platforms. Method: Employing a qualitative case study methodology, this research investigated the learning dynamics and outcomes observed within two distinct cohorts of students, totalling eight participants. These students engaged in a nine-session program situated within a classroom environment, characterized by collaborative gameplay and structured game analysis. Central to this approach was the utilization of a metalanguage framework specific to digital play. Various data collection techniques were employed, encompassing participant observation, interviews, electronic portfolios, and field notes, all of which underwent thematic analysis for comprehensive interpretation. Findings: The results uncovered the nuanced learning dynamics and outcomes pertaining to students' multimodal literacy across functional, critical, and aesthetic domains. This was achieved through a detailed examination of digital gameplay, focusing on representation, engagement, and organization perspectives. Implications: This research provided empirical evidence supporting the recognition of digital games as legitimate and authentic texts that extend the narrative scope of students' literacy endeavours beyond traditional confines, thereby warranting increased pedagogical emphasis within literacy education settings. Such emphasis is essential for cultivating adolescents' multimodal literacy skills, priming them for adept critical engagement with future media contexts. Moreover, the study offers practical insights for educators, facilitating the assessment of digital gameplay as a form of literacy practice and its subsequent integration within multimodal literacy instructional frameworks.